Development and Evaluation of a Liquid Formulation of Trichoderma viride as a Bio-Pesticide for Pest Management - Sorathiya, Kalpesh; Sorathiya, Kuldip; Kalariya, Shreya; Patel, Lensi (International Journal of Applied Sciences and Biotechnology, 2023)
The use of bio pesticides in modern agriculture is acknowledged as an efficient substitute for chemical pesticides because they are based on natural ingredients. Fungal bio pesticides are the most widely used and have a lot of success stories among the various bio pesticides. Trichoderma is a genus of filamentous fungi that has several promising bio control agents for different plant diseases. Trichoderma viride uses a variety of strategies to fight plant diseases, including high reproducibility, adaptability, production of enzymes and antibiotics, capacity to colonies the rhizosphere, and significant inhibitory effects against phytophathogenic fungi. The prospective Trichoderma viride isolates are produced utilizing various carriers either through solid or liquid fermentation technologies, however solid fermentation produces the highest levels of reproductive capacity. High cost of substrate and storge methods are major problems to accelerate the production. The aim of our research is commercially available substrates were carried out to screen out stabilization of formulations for small scale production of Trichoderma vride. Int. J. Appl. Sci. Biotechnol. Vol 11(2): 60-65.